3D face alignment and registration in the presence of facial expression diﬀerences. Issue 4 (20th May 2013) - Pintavirooj, Chuchart; Cohen, Fernand S.; Tosranon, Prasong
Abstract This paper deals with the problem of 3D alignment of faces in the presence of some facial expression changes. The data are three dimensional and obtained using a laser scanner. Our approach is based on the diﬀerential geometry of the surface and computes the intrinsic local ﬁducial points on the surface and on curves that reside on the surface. Because these ﬁducial points are local, they allow partial alignment, where part of the face is viewed. Moreover, since the ﬁducial points are relatively aﬃne‐invariant to local aﬃne transformations, they allow matching and alignment when facial expression changes aﬀect part of the face. A fast, noniterative alignment procedure is presented in this paper that establishes reliable correspondences between ﬁducial points without any prior knowledge of the overall nonlinear global transformation that takes place after the changes in facial expressions. This is achieved through the construction of a set of ordered novel absolute local aﬃne invariants. With enough ﬁducial points set as correspondents, the overall nonlinear transformation is computed and the face before and after the transformation are aligned. For comparison, we also compare the alignment performance of our method with that of the iterative closest point (ICP) method and the coherent point drift (CPD) method which is based on the Gaussian mixture model by looking at the between‐to‐within variation (signal‐to‐noise ratio, SNR) between these two classes (match vs nonmatch) based on the average alignment errors for the genuine matches and nonmatches, normalized by their respective within variation, and by running it on the 3D face database GavabDB. The separation between the true match and nonmatch is best for our zero‐torsion method (SNR of 1.2), followed by the ICP method (SNR of 0.37)and the CPD method (SNR of 0.15). It is interesting to observe here that, although the alignment error for the true match cases is lowest for the CPD method, it is also extremely low for the nonmatch cases, which would mean that the method would force a query into a wrong face, yielding poor speciﬁcity (lots of false alarms). © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.